Prevalence of Myopia in Children and Adolescents: A Systematic Review of Malaysian Prevalence Studies - Tan, Eudocia Shu Yi; Agarwal, Puneet; Teng, Cheong Lieng (Malaysian Journal of Medical Sciences, 2026)
Background: Myopia is a common eye problem that has increased in prevalence worldwide, including in Malaysia. This study aimed to determine the prevalence of myopia among children and adolescents aged 0 to 18 years in Malaysia and its associated sociodemographic factors.Methods: The preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline were used in this study. We searched PubMed and Scopus, supplemented by a targeted Google Scholar search, for studies published from 1990 to 2024 on the prevalence of myopia in Malaysia. Myopia was defined as a refractive error ≥ –0.50 D.Results: The meta-analysis included 14 quality-assessed studies from seven states in Malaysia, covering 13,367 children and adolescents. The overall pooled prevalence of childhood myopia from 1990 to 2024 was 17.18% (95% CI: 9.98, 25.86). The prevalence of myopia was notably lower among children aged 0 to 6 years at 2.54% (95% CI: 0.66, 5.60) than among children aged 7 to 12 years at 26.48% (95% CI: 17.29, 36.84) and adolescents aged 13 to 18 years at 42.71% (95% CI: 26.80, 59.44). The prevalence of myopia was higher in females than in males (odds ratio: 1.20; 95% CI: 1.09, 1.32). The Chinese population had the highest prevalence of myopia at 44.62% (95% CI: 35.94, 53.47) compared with other ethnicities.Conclusion: Our findings indicate that at least four in 10 children and adolescents aged 13 to 18 years are likely to have myopia in Malaysia. Targeted clinical and public health interventions should prioritise high-risk groups, particularly females, individuals of Chinese ethnicity, and those aged 7 to 18 years.